Historical Origins and Current Concepts of Wound Debridement. Issue 2 (1st June 2011) - Guthrie, HC; Clasper, JC
Abstract : In the late 18 th Century wound debridement consisted of incision of skin and deep fascia to release the swelling associated with ballistic injury, however extremity war wounds were more usually managed non-operatively or by amputation. During the First World War debridement was redefined to include excision of all non-viable and foreign material. In the modern era it has been proposed that wounds contain a zone of injured tissue which is not obviously non-viable at the initial debridement. Debridement which preserves this tissue has been described as marginal debridement. Wounds sustained in close proximity to explosions have an extensive zone of injury. Preservation of traumatised tissue may be beneficial in terms of limb salvage and limb reconstruction. Equally the complexity and contamination of these wounds, as well as the physiological frailty of the casualty, may make complete debridement in one sitting an unachievable goal. Where traumatised tissue has been left during debridement it must be reassessed at around 48 hours in order to reduce the risk of infection. Evacuation timelines and logistic infrastructure currently support serial marginal debridement but in future conflicts this may not be the case.